Exploring the Opportunities and Forms of Institutional Support for Dual-Career Student-Athletes at Universiti Pendidikan Sultan Idris (UPSI) - Muhammad Muqri Aiman; Zulakbal Abd Karim; Amin Akbar; Yasmin Athirh; Sumeira Rajab (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2026)
Student-athletes in higher education are required to balance demanding academic responsibilities with intensive training and competitive sports commitments. This study aims to explore the opportunities and forms of institutional support experienced by student-athletes at Universiti Pendidikan Sultan Idris (UPSI) in managing their dual roles as students and athletes. This dual-career pathway often leads to time constraints, role conflict, and psychological pressure, particularly when institutional support is inconsistent. This study adopts a qualitative approach to obtain an in-depth understanding of the lived experiences of student-athletes in the university context. Data were collected through semi-structured, in-depth interviews with 15 undergraduate student-athletes from various sports disciplines at UPSI, transcribed using Sonix.ai, and thematically analyzed using ATLAS.ti 24. The thematic analysis reveals that institutional support, particularly academic flexibility, lecturers’ understanding, access to facilities, training and mentoring, financial assistance, and peer support, plays a central role in maintaining engagement in both domains. The findings highlight the importance of academic flexibility, lecturers’ understanding, and institutional support. In conclusion, effective institutional support is important for balancing academic and athletic commitments. This study deepens understanding of student-athletes’ experiences in a Malaysian public university and provides implications for strengthening support to enhance academic success, well-being, and holistic development.